SISTEM PAKAR REKOMENDASI JURUSAN MENGGUNAKAN METODE FORWARD CHAINING - Erika Anjani Putri; Ade Eviyanti; Hindarto Hindarto (Politeknik Bisnis Indonesia, 2023)
SMK Antartika 2 Sidoarjo provides instruction in seven different areas of competence. With so many choices of majors, it causes several problems in choosing majors, including not in accordance with interests, or not knowing their interests and potential. Expert Systems are one part of artificial intelligence that is created to help make decisions in solving problems like experts. The Forward chaining method provides conclusions that begin by using rules that relate facts. The Department Recommendation Expert System using the Forward chaining method that was built runs well. This system is designed to assist new SMK students in determining the majors to be taken according to the talent interests of new students by providing department recommendations, based on the results of testing department recommendations in the system with the same results of determining the majors of interest resulting in a percentage of 90%. Based on black box testing that has been carried out on this system in accordance with what was expected by 40 respondents, the percentage of department recommendations was 89.33%, and ease of access was 93.33%. The expert system is made based on a website that can be accessed online and can be used at any time.